The effect of subcutaneous immunoglobulin replacement therapy on serum IgG levels in patients with primary immunodeficiency - Selime Özen Bölük; Nesrin Gülez; Canan Karkıner; Özgen Soyöz; Figen Çelebi Çelik; Mehmet Şirin Kaya; Idil Akay Hacı; Ilke Taşkırdı; Ömer Akçal; Ferah Genel (Trends in Pediatrics)
Objective: In a large group of patients with primary immunodeficiency (PID), immunoglobulin replacement therapy is critical for infection control. There are two main methods of immunoglobulin replacement intravenous (IVIG) and subcutaneous (SCIG). The aim of this study was to determine the efficacy of SCIG by comparing IgG levels and frequency of infections obtained during SCIG replacements in patients with PID with those obtained during IVIG administration.